Hadits Prespektif Fazlur Rahman: Pencandraan Epistemologis Filsafat Ilmu Fazlur Rahman Atas Hadits - Masyhadi Masyhadi (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2017)
Fazlur Rahman's view brings logical consequence, that is, it is necessary to understand the Prophet's behavior in the frame of context and its sociological-historical framework. In other words, the sunnah of the prophet needs to be regarded as an example, not as an absolute special content.